PENGELOLAAN PERKULIAHAN MATA KULIAH KEWIRAUSAHAAN DALAM MENINGKATKAN MINAT BERWIRAUSAHA MAHASISWA EBIS IAIN MADURA - Saiful Hadi; Dwi Anisa (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2020)
Entrepreneurial interest of each individual arises along with one's efforts to gain an understanding of entrepreneurship obtained through daily activities of doing business independently in the surrounding environment, through knowledge from lectures both aspects of entrepreneurial theory and entrepreneurial practice as academic demands so that it impacts on the growth of entrepreneurial motivation. This research was conducted qualitatively by tracing the lecture activities of study program students at the Faculty of Business Economics IAIN Madura. The results showed that; first, designing lectures as well as possible that refers to the syllabus, preparing references and theories, students are encouraged to take an active part in class. Second, the implementation of entrepreneurship courses, namely the existence of discussion activities and field practice. During the discussion the students were equipped with knowledge about entrepreneurship, business, which was then strengthened by holding business practices outside the classroom. Third, the level of success of the entrepreneurship course courses is the emergence of creative and innovative ideas for students to carry out small entrepreneurial activities on campus such as selling food cakes to other students as a form of entrepreneurial interest.